Dan Williams's Retrieving the Tradition and Renewing Evangelicalism: A Primer for Suspicious Protestants - Ferguson, Everett (Scottish journal of theology, 2002)
Dan Williams challenges the ‘historylessness’ of much contemporary evangelicalism and pleads for a recovery of the great Tradition as a way of ‘renewing evangelicalism’. I agree with the need to pay attention to history but am not so optimistic about its resulting in renewal and find problems in the statement of the case that require further exploration. To follow Tradition is to affirm the authority of scripture. The Rule of Faith itself was a summary of the teaching found in scripture. Theological programmes other than the ‘Bible alone’ have not been notably successful in overcoming division. The early creeds and councils may be accepted as confessions of faith but not as tests of fellowship.